Challenges in the Era of Modernity and Post-Modernity (Belief and Non-Belief to Science) - mohammad abbaszadeh; elnaz panahi (توسعه اجتماعی)
When we discuss about differences between modernism and postmodernism, we believe the differences between science and non-science too. On one side we can talk about Karl Popper who believe in science and the other side consist of people such as and Feyerabend and Kuhn who not believe to the science. In this paper an attempt has been done according to different aspect of discussion.